Assessing the amount of total Coliform and the amount of Heavy Metals, Chromium and Lead from household water from different industrial zones of Dhaka Division (Tejgaon and Tongi) - Islam, Isra Binte; Alamgir, Shamaila (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Science in Microbiology, 2019.